1999
DOI: 10.1111/j.1479-828x.1999.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus. At What Time Should the Postprandial Glucose Level be Monitored?

Abstract: For women with GDM, monitoring either 1 hour or 2 hours postprandially led to similar outcomes. This would suggest that the ADIPS recommendations are equivalent and therefore women can choose the most convenient time for their postprandial monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…There is also no consensus as to the optimal timing of the postprandial test [15]. Traditionally, in the guidelines for care of nonpregnant diabetic patients, glucose monitoring 2 hours after eating has been recommended because of fear of hypoglycemia due to the peak action of human regular insulin.…”
Section: Importance Of Monitoring Postprandial Glucose Levels In Gestmentioning
confidence: 99%
“…There is also no consensus as to the optimal timing of the postprandial test [15]. Traditionally, in the guidelines for care of nonpregnant diabetic patients, glucose monitoring 2 hours after eating has been recommended because of fear of hypoglycemia due to the peak action of human regular insulin.…”
Section: Importance Of Monitoring Postprandial Glucose Levels In Gestmentioning
confidence: 99%
“…Because the peak postprandial glucose concentration is 1 h after eating (11), a rapid-acting insulin analog that reaches peak concentration at about 1 h after injection would be ideal. Data on nonpregnant diabetic patients document that the rapid-acting insulin analog, insulin aspart, peaks at 40 to 60 min after injection and thus can be used to blunt the peak postprandial glucose concentrations (15). Before insulin aspart can be prescribed in pregnancy, the safety and efficacy of this insulin analog will need to be studied.…”
mentioning
confidence: 99%
“…Assessment of blood glucose can be undertaken at either 1 hour or 2 hours postprandially, but no study to date has demonstrated the superiority of either approach (24)(25)(26). Controlled trials to identify ideal glycemic targets have not been performed.…”
Section: How Should Blood Glucose Be Monitored In a Woman With Gdm?mentioning
confidence: 99%